1999
DOI: 10.1007/s004250050504
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the location of polyphenol oxidase in potato ( Solanum tuberosum L.) tuber during cell death in response to impact injury: comparison with wound tissue

Abstract: In order to elucidate the nature of the response of potato to impact injury at the biochemical level, changes in the location of the enzyme responsible for the discoloration, polyphenol oxidase, were determined using immunogold location with an antibody specific for potato tuber polyphenol oxidase. Tissue printing revealed that the enzyme was distributed throughout the tuber. Following impact injury, both tissue printing and quantitative electron microscopy indicated that there was no increase in the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 26 publications
2
12
0
2
Order By: Relevance
“…Although it is generally agreed that PPO is plastid located, the site at which it is present in potato tubers is not entirely clear. PPO in undamaged tissue was located to starch grains and the cytoplasm, but upon several hours after mechanical bruising the PPO becomes more generally distributed including in the vacuolar region (Partington et al, 1999). This is presumably due to breakdown of membrane integrity and thus direct evidence of ''leakage'' from defined sites was demonstrated, using immuno-gold localisation integrity appearing in the cytoplasm.…”
Section: Ppo In Diverse Generamentioning
confidence: 96%
“…Although it is generally agreed that PPO is plastid located, the site at which it is present in potato tubers is not entirely clear. PPO in undamaged tissue was located to starch grains and the cytoplasm, but upon several hours after mechanical bruising the PPO becomes more generally distributed including in the vacuolar region (Partington et al, 1999). This is presumably due to breakdown of membrane integrity and thus direct evidence of ''leakage'' from defined sites was demonstrated, using immuno-gold localisation integrity appearing in the cytoplasm.…”
Section: Ppo In Diverse Generamentioning
confidence: 96%
“…Some increase in heterochromatin was also observed in mutant mesophyll cell nuclei, but the increase was not as great as that observed in BS nuclei (data not shown). The most common morphological change noted in plant PCD studies, namely the presence of small cytoplasmic vacuoles in dying cells, followed by cytoplasmic condensation (Bestwick et al, 1997;Kosslak et al, 1997;Mittler et al, 1997;Partington et al, 1999;Wang et al, 1999) was observed in mesophyll cells. In addition, the central vacuole seemed to have disappeared in all cells adjacent to pinprick wounds, suggesting that tonoplast collapse (Jones, 2001) may also be a feature of cell death in lls1 plants.…”
Section: Death Of Lls1 Cells Is Mediated By Chloroplastsmentioning
confidence: 99%
“…[6] Partington et al [7] reported that bruised tissue undergoes cell death in contrast to wounded tissues showing continued induction of defense proteins, tissue repair and no cell death. About 3 h after impact, cell death was initiated and coincided with de-compartmentalization, the appearance of lipid peroxides and melanin production.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, bruising induces death and dehydration of all the cells, which leave a large space indicating loss of effective barrier against infection. [7] Bruise extent is usually described in terms of bruise volume, which effects product quality. [3] To determine the damage susceptibility of pears, research is needed using the size of the bruises.…”
Section: Introductionmentioning
confidence: 99%